1974
DOI: 10.1177/00220345740530052101
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Periodontal Receptors to the Masseteric Silent Period

Abstract: Quadrant local anesthesia was sequentially administered to the maxillary and mandibular teeth and periodontium in three healthy individuals. After anesthesia the duration of the silent period was shortened. Total anesthesia of all quadrants abolished the silent period in every individual, demonstrating that sensory impulses from periodontal receptors provide a major source of inhibition, and disfacilitation or active inhibition from intact muscle receptors is insufficient to produce a silent period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Watt etal /• d ucing reflex changes in the elevator muscle activity following tooth contact. Bessette, Mohl & Bishop (1974) consider that the periodontal receptors provide a major source of inhibition contributing to the silent period in masseter muscles, but because of the small size of their sample (3 men) the evidence which they obtained may be insufficient to sustain their conclusion. Some believe that the Golgi organs of the tendons and ligaments are chiefly responsible for the inhibition of muscle activity and others that the muscle spindles are chiefly involved.…”
Section: Introductionmentioning
confidence: 97%
“…Watt etal /• d ucing reflex changes in the elevator muscle activity following tooth contact. Bessette, Mohl & Bishop (1974) consider that the periodontal receptors provide a major source of inhibition contributing to the silent period in masseter muscles, but because of the small size of their sample (3 men) the evidence which they obtained may be insufficient to sustain their conclusion. Some believe that the Golgi organs of the tendons and ligaments are chiefly responsible for the inhibition of muscle activity and others that the muscle spindles are chiefly involved.…”
Section: Introductionmentioning
confidence: 97%
“…There is evidence that the teeth and their surrounding tissues are protected from excessive forces during clenching by the inhibitory efl"ect of the periodontal receptors on the masseteric motoneurones (Bessette, Mohl & Bishop, 1974). The inhibition from periodontal receptors which may be correlated to the clenching force during biting may influence the duration of the so-called silent period (SP) (Bessette, Bishop & Mohl, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical stimuli activate a number of receptors that may have different synaptic connections to the motoneuronal pool of the masticatory muscles [1]. nevertheless, most likely, that the bite force reflex is regulated by a periodontal feedback to protect the masticatory system from being damaged, as it has been confirmed that PMRs significantly contribute to the inhibition of jaw-closers [1,4,8,9,12,14,17,18]. these results further highlight the importance of the RbF value for the modulation of the strength of the jaw reflex; as we found that the higher RbF values produced stronger net inhibitory reflex.…”
Section: Discussionmentioning
confidence: 99%
“…local anaesthetic blocks have been used to identify the reflex responses that originate from PMRs [4,[12][13][14]. several studies have illustrated that PMRs are responsible for the majority of the reflex responses of the human jaw muscles and that PMRs have much more powerful inhibitory effects on masseter muscles than previous suggestions [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%